2007
DOI: 10.1002/j.0022-0337.2007.71.11.tb04415.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Delphi Technique in a Consensual Curriculum for Periodontics

Abstract: Periodontics has experienced several important conceptual changes in the last few decades. As such, it is important to have a periodontics curriculum built upon the expertise of specialists in that discipline and reflecting those changes. The main goal of this study was to attain a consensus, through the use of the Delphi technique, on the topics that should be included in a periodontics curriculum for undergraduate dental students. A sample of periodontics lecturers from nine dental schools in two Brazilian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…16 It has been used by other groups and disciplines to develop curricula, competencies, and objectives. [17][18][19] A limitation of our approach to defining patient care EPAs is that we began with internal testing within a single residency program. Therefore, despite drawing on previously published lists, our list was influenced by the setting, clinical practice, faculty, and philosophy of our program.…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been used by other groups and disciplines to develop curricula, competencies, and objectives. [17][18][19] A limitation of our approach to defining patient care EPAs is that we began with internal testing within a single residency program. Therefore, despite drawing on previously published lists, our list was influenced by the setting, clinical practice, faculty, and philosophy of our program.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to another study on the development of a curriculum for an ‘Advance General Dentistry’ training programme , the Delphi panel used in the present study was heterogeneous and included students' view. A guiding framework was not present in previous studies that used a Delphi process to facilitate changes in the curriculum in dentistry. The final list of outcomes for the orthodontic postgraduate students in Cardiff is organised in accordance with the three‐circle model to classify learning outcomes by Harden et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using a Delphi approach have noted some disadvantages : the absence of any guiding framework in changing the curriculum (vertical alignment); the absence of communication between different groups (students, teachers, course organisers, etc.) that should be involved in changing the curriculum (horizontal alignment); the absence of a key component of the curriculum, such as assessment. …”
Section: Introductionmentioning
confidence: 99%
“…Given the Delphi method's flexible format and prior use to develop healthcare curricula (Turner and Weiner 2002;Walley and Webb 1997;Fried and Leao 2007;Penciner et al 2011;Waggoner et al 2016), we identified the Delphi method as a suitable way to survey a nationally representative cohort of medical educators about SaT curricular priorities. To our knowledge, this is the first national Delphi study carried out for SaT or RaT programs.…”
Section: The Delphi Methodsmentioning
confidence: 99%